Perbedaan Tingkat Daya Tahan Kardiovaskular Antara Siswa Perokok dan Tidak Perokok : Studi Kasus Pada Siswa Ekstrakurikuler Olahraga SMAN 1 Parang - Agil Suryati Putra; Ratna Candra Dewi; Soni Sulistyarto; Testa Adi Nugraha (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Smoking has become a habit and is a public health problem throughout the world, especially among teenagers. Smoking in adolescence can interfere with fitness, one of the effects experienced is a decrease in cardiovascular endurance. The aim of this study was to determine the level of cardiovascular endurance of male extracurricular sports students who were smokers and non-smokers at SMAN 1 Parang. The design of this research is comparative research. The techniques used to collect data are filling out questionnaires and VO2Max tests. The subjects used in the research were 22 boys' extracurricular sports students at SMAN 1 Parang, divided into 10 futsal extracurriculars and 12 volleyball extracurriculars. The instrument used is the Multistage Fitness Test (MFT). Then, the data analysis technique used is to carry out data prerequisite tests (normality test and data homogeneity test) and hypothesis test (Independent t-test) and in analyzing the data from this research using SPSS version 26 software. Based on the research results and data analysis there are differences The VO2Max level which can be seen from the average value is 33.9 for smoking students and 42.1 for non-smoking students. So it can be concluded that the VO2Max level of non-smoking extracurricular sports students is better than smokers' extracurricular sports students. So it can be said that each student has a different VO2Max level.